Flower-like Co3Ni1B nanosheets based on reduced graphene oxide (rGO) as an efficient electrocatalyst for the oxygen evolution reaction. (27th June 2022) - Ding, Junxia; Yue, Ruimei; Zhu, Xiaolun; Liu, Wentong; Pei, Hebing; He, Simin; Mo, Zunli
Abstract : Flower-like Co3Ni1B nanosheets based on a reduced graphene oxide electrocatalyst exhibit a better OER performance than commercial RuO2 . Abstract : The preparation of efficient and stable non-noble metal electrocatalysts for the oxygen evolution reaction during the electrolysis of water is extremely significant. Herein, reduced graphene oxide (rGO) supported flower-like Co3Ni1B nanosheets were successfully synthesized via a static precipitation method at room temperature and used as an efficient oxygen evolution reaction (OER) electrocatalyst. This two-dimensional (2D) catalyst has a high specific surface area, which exposes a large number of active sites. The rGO improves the electrical conductivity and promotes fast electron transfer during the OER process. In alkaline medium, the Co3Ni1B–rGO catalyst exhibits superior OER activity with a low overpotential of 318 mV at a current density of 10 mA cm −2, and stability up to at least 16 hours. This work provides insights into the facile design and preparation of 2D amorphous boride composites for energy transitions.